2003
DOI: 10.2202/1544-6115.1003
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Correction in Pedigree Analysis

Abstract: Usually, a pedigree is sampled and included in the sample that is analyzed after following a predefined non-random sampling design comprising several specific procedures. To obtain a pedigree analysis result free from the bias caused by the sampling procedures, a correction is applied to the pedigree likelihood. The sampling procedures usually considered are: the pedigree ascertainment, determining whether a population unit is to be sampled; the intrafamilial pedigree extension, determining what part of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Previous studies have explored the proportion of apparently sporadic cases for polygenic diseases [3] and the effects of ascertainment bias on pedigree sampling and parameter estimates in linkage studies of complex disease [28,29] . For many complex diseases, familiality rates are of the order of 5 to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the proportion of apparently sporadic cases for polygenic diseases [3] and the effects of ascertainment bias on pedigree sampling and parameter estimates in linkage studies of complex disease [28,29] . For many complex diseases, familiality rates are of the order of 5 to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…We use notation that is similar to that used by Ginsburg et al [2003]. Let t denote a true pedigree (both its structure and the trait and marker phenotypes).…”
Section: Methods Basic Notationmentioning
confidence: 99%
“…Vieland and Hodge [1996] stated that the problem of ascertainment correction in linkage analysis is ''fundamentally intractableynot only for lod scores per se, but for any likelihood-based method for linkage or joint linkage/segregation analysis.'' Recently, Ginsburg et al [2003] developed a general theory for obtaining an appropriate likelihood that allows for a preplanned sampling design. We showed that for segregation analysis, an appropriate sampling correction can be made either in an ascertainment-model-based (AMB) approach by conditioning the pedigree likelihood on the structure of the pedigree data relevant to sampling (RS), a term we define more fully below (see Joint Segregation and Linkage Analysis), or in an ascertainment-model-free (AMF) approach provided that all phenotypic data on the pedigree members RS are observed.…”
Section: Introductionmentioning
confidence: 99%
“…If the probability that an individual in the proband sampling frame becomes a proband is very small we have the ideal condition known as single ascertainment. The problem of modeling ascertainment accurately is quite difficult and has generated some controversy [30,31] .…”
Section: Ascertainmentmentioning
confidence: 99%